Appraisal the Key Factors of SCQM using a Combined Approach of SWARA-FISM - Mehdi Ajalli; Mohammad Mahdi Mozaffari (International Journal of Supply Chain Management, 2018)
Researchers in recent years have introduced supply chain quality management as a new concept and use it considered as the last step in the move toward